BLENDED LEARNING: PELUANG DAN TANTANGAN PELAKSANAANNYA PADA SEKOLAH DASAR - Salim, Nur Agus (Academy of Education Journal, 2023)
This research aims to explore the opportunities and challenges in implementing blended learning in elementary schools in Samarinda during the new normal period, using library research or literature review methodology. The main focus is to provide a comprehensive understanding of how blended learning can be implemented effectively, taking into account factors such as infrastructure readiness, teacher competency, and student engagement and motivation. The research results show that implementing blended learning in elementary schools offers valuable opportunities such as greater personalization of learning, development of student independence, integration of active learning through a combination of in-class and online methods, improvement of students' technology skills, and flexibility in accessing materials. However, this method also faces significant challenges, including limited access to technology among students, the need for more intensive teacher training, challenges in motivating students, and difficulties in assessing learning and ensuring the quality of online materials. The conclusions of this study underscore the importance of effectively addressing these challenges to create a conducive learning environment. Strategies that involve improving technological infrastructure, continuous teacher training, development of quality learning materials, and effective motivational approaches for students are needed.